2012
DOI: 10.1134/s003602361206006x
|View full text |Cite
|
Sign up to set email alerts
|

Microemulstion synthesis of powders of water-soluble energy-saturated salts

Abstract: 769Microemulsion (micellar) synthesis is a popular method and is widely used for preparing nanoparticles of metals [1], oxides [2], and sparingly soluble salts [3,4]. The advantages of this method include: (1) the ease of synthesis; (2) a narrow particle size distribution function of the product; (3) a feasibility of preparing particles of complex composition, multilayered, hybrid, and other types of particles [5]; and (4) a good knowledge of the micellar and microemulsion struc ture. Unfortunately, there only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…• C) than the crystal (333 • C) [3]. It was demonstrated that the intense mechanical treatment of coal (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…• C) than the crystal (333 • C) [3]. It was demonstrated that the intense mechanical treatment of coal (i.e.…”
Section: Introductionmentioning
confidence: 99%